ANALISIS PENGARUH LITERASI KEUANGAN SYARIAH TERHADAP KEPUTUSAN GENERASI Z MENABUNG PADA BANK SYARIAH INDONESIA (STUDI KASUS MASYARAKAT KECAMATAN HARAU KABUPATEN LIMA PULUH KOTA) - Dira Indriani; Cahya Agung Mulyana (Jurnal Ekonomi dan Bisnis, 2025)
This study is entitled "Analysis of the Influence of Sharia Financial Literacy on Generation Z's Decision to Save at Bank Syariah Indonesia (Case Study of the Harau District Community, Lima Puluh Kota Regency)". Compiled by Dira Indriani NIM 3320322 Sharia Banking Study Program, State Islamic University (Uin) Sjech M. Djamil Djambek Bukittinggi. The purpose of this study was to determine how much influence sharia financial literacy has on the decision of generation z to save at Indonesian sharia banks. The type of research used in this study is quantitative descriptive research. The data used are primary and secondary data. The population in this study is generation z in Harau District with a sample of 100 respondents using data collection techniques with observation, questionnaires and documentation. The results of the study indicate that the variable of Islamic financial literacy has a significant effect on the decision of generation z to save at Indonesian Islamic banks, the independent variable (Islamic financial literacy) is able to contribute to influencing the dependent variable (the decision of generation z to save at Islamic banks) by 0.505 or 50.5% while the remaining 49.5% (100% - 50.5% = 49.5%) is influenced by other variables outside the regression model that analyzes the decision of generation z to save at Indonesian Islamic banks.